MISOPROSTOL AS PREVENTION OF POSTPARTUM HEMORRHAGE: A TEN YEARS SYSTEMATIC REVIEW - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Postpartum Haemorrhage (PPH) is commonly defined as a blood loss of 500 ml or more within 24 hours after birth. PPH is the leading cause of maternal mortality in low-income countries and the primary cause of nearly one quarter of all maternal deaths globally. The aim: This study aims to show about misoprostol as prevention of postpartum hemorrhage. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 23 articles, whereas the results of our search on SagePub brought up 39 articles. The results of the search conducted for the last year of 2014 yielded a total 13 articles for PubMed and 27 articles for SagePub. The result from title screening, a total 5 articles for PubMed and 14 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Other injectable uterotonics and misoprostol are recommended as alternatives for the prevention of PPH in settings where oxytocin is unavailable.